Auf dem Weg zur Energiewende Die Entwicklung der Stromproduktion aus erneuerbaren Energien in Deutschland ; eine Studie aus dem Soziologischen Forschungsinstitut Göttingen (SOFI) - Mautz, Rüdiger (Universitätsverlag Göttingen, 2008)
Electricity generation from renewable sources of energy has had a long history in Germany and is highly topical. This paper deals with both aspects. A sociological analysis of technology shows how innovative technologies gradually emerged from the Utopian vision of 'velvet' energies, which became the basis of the rapidly growing regenerative electricity production. The second aspect of the paper is an analysis of the growing potential - as well as possible obstacles - of regenerative energies. The expansion of energy production from renewable sources and the tendency towards the concentration of such installations (e.g. large wind farms or solar parks) is increasingly met with opposition from the public. In addition, it is felt that considerable changes in the energy sector can only be successful if its promoters become more active.